Summaries. Issue 1 (March 2016) - Unknown
Abstract : The World's Poultry Science Journal is indebted to Prof J.A. Castello, Prof D.K. Flock, Dr D. Grastilleur, Dr S. Cherepanov and Prof N. Yang for the translations of these summaries.